A STUDY OF THE REMOVE CATIONIC AND ANIONIC DYES IN AQUEOUS SOLUTION BY A NEW NATURAL CLAY - Tamimi, Malika; Bougdour, Nadia; Alahaine, Said; Sennaoui, Asma; Assabbane, Ali (International Journal of Engineering Technologies and Management Research, 2018)
The objective of this work is to study the possibility of eliminating both dyes Methylene Blue (MB) and Congo Red (CR) by adsorption on natural clay of the region of Agadir and determine the different reaction parameters effect on the proceeds. Orientation tests have been carried out in distilled water solutions. The results of the kinetics of adsorption showed that optimal contact time is 60 min; it corresponds to a maximum removal rate of MB and CR respectively of the order of 99% and 75%. Increased adsorbent ratio (0,1 à 2 g / l) improves the removal efficiency of the CR especially dyes for an initial concentration of 10 mg/l. NaNO3 salt and pH of the medium greatly influence the CR of retention. Whatever the reaction parameter tested; it appears that the clay has a good efficiency for the retention of two dyes.